A influência da espiritualidade/religiosidade na subjetividade de jovens homossexuais: uma proposta de compreensão fenomenológica - Silva, Laionel Viera da (2016)
Historically in our Western context, human sexuality has been governed by different scientific and religious perspectives, in which homosexuality has been identified by values close to Christianity as something "different" from the ordinary. This strangeness is generating a subjective tension in homosexual men and women, including as they relate to spirituality/religiosity. While religiosity tends to relates to the institutional rules of a religious tradition, spirituality provides a search for sense and self-knowledge to human life. Our main objective is to investigate the spirituality/religiosity of influence in the subjectivity of young homosexuals. Thus, the research follows divided into three parts: an overview of homosexuality in the Western historical context, especially in Brazil today; analysis of the relationship between homosexuality and spirituality; and spirituality of contributions in the subjectivity of gay university students. This study was developed through a phenomenological field research. Study participants were three men and three women homosexuals, answering the question triggering "how you perceive the presence of sexuality in your spirituality?". In addition, respondents also a sociodemographic questionnaire. Through this study it was possible to understand some of the spirituality of the senses gay subjectivity, such as freedom, well-being and self-acceptance of their sexuality. For a better understanding of the relationship between religiosity / spirituality and homosexuality, it is pertinent to develop new research that seeks to understand the interaction of these themes from other perspectives.